Comparison of facet joint activity on 99mTc-MDP SPECT/CT with facet joint signal change on MRI with fat suppression - Vance T. Lehman; Robert C. Murphy; Louis A. Schenck; Rickey E. Carter; Geoffrey B. Johnson; Amy L. Kotsenas; Jonathan M. Morris; Mark A. Nathan; John T. Wald; Timothy P. Maus (Diagnostic and Interventional Radiology, 2016)

(untitled)
PURPOSEWe compared signal change on magnetic resonance imaging (MRI) with fat suppression and bone scan activity of lumbar facet joints to determine if these two imaging findings are correlated.METHODSWe retrospectively identified all patients who underwent imaging of the lumbar spine for pain evaluation using both technetium-99m methylene disphosphonate single-photon emission computed tomography/computed tomography (99mTc-MDP SPECT/CT) and MRI with at least one fat-suppressed T2- or T1-weighted sequence with gadolinium enhancement within a 180-day interval, at our institution between 1 January 2008 and 19 February 2013. Facet joint activity on 99mTc-MDP SPECT/CT and peri-facet signal change on MRI were rated as normal or increased. Agreement between the two examination types were determined with the κ and prevalence-adjusted bias-adjusted κ (PABAK) statistics.RESULTSThis study included 60 patients (28 male, 47%), with a mean age of 49±19.7 years (range, 12–93 years). The κ value indicated no agreement between 99mTc-MDP SPECT/CT and MRI (κ=–0.026; 95% confidence interval: –0.051, 0.000). The PABAK values were fair to high at each spinal level, which suggests that relatively low disease prevalence lowered the κ values. Together, the κ and PABAK values indicate that there is some degree of intermodality agreement, but that it is not consistent.CONCLUSIONOverall, facet joint signal change on fat-suppressed MRI did not always correlate with increased 99mTc-MDP SPECT/CT activity. MRI and 99mTc-MDP SPECT/CT for facet joint evaluation should not be considered interchangeable examinations in clinical practice or research.